2006
DOI: 10.1093/cercor/bhl027
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Retinotopic Mapping: The Spatial Representation of Objects in the Human Lateral Occipital Complex

Abstract: The spatial representation in the human ventral object-related areas (i.e., the lateral occipital complex [LOC]) is currently unknown. It seems plausible, however, that it would diverge from the strict retinotopic mapping (characteristic of V1) to a more invariant coordinate frame, thereby allowing for reliable object recognition in the face of eye, head, or body movement. To study this, we compared the fMRI activation in LOC when object displacement was limited to either the retina or the screen by manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
75
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 35 publications
16
75
2
Order By: Relevance
“…Similarly, the EBA preferred lower visual field stimuli to both foveal and upper visual field stimuli, which activated the region equally. These findings, like earlier reports of contralateral biases in object-selective regions (13)(14)(15)(16) do not fit within the fovea/periphery framework, and it is not clear how the computational-demands hypothesis (35) could account for them.…”
Section: Why Do Category-selective Regions Come In Pairs?contrasting
confidence: 74%
See 2 more Smart Citations
“…Similarly, the EBA preferred lower visual field stimuli to both foveal and upper visual field stimuli, which activated the region equally. These findings, like earlier reports of contralateral biases in object-selective regions (13)(14)(15)(16) do not fit within the fovea/periphery framework, and it is not clear how the computational-demands hypothesis (35) could account for them.…”
Section: Why Do Category-selective Regions Come In Pairs?contrasting
confidence: 74%
“…At the most general level, some of these regions demonstrate contralateral field biases (13)(14)(15)(16), and some of them [e.g., the parahippocampal place area (PPA)] respond more strongly to stimuli presented in the periphery, whereas others [e.g., the fusiform face area (FFA)] respond more strongly to foveal stimuli (17,18). Studies conducted with retinotopic mapping (19,20) have shown object-selective responses in certain retinotopically defined regions, although the degree to which these maps overlap object-selective cortex is not yet known.…”
Section: Since Ungerleider and Mishkin [Underleider Lg Mishkin M (1982)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported that some visual areas represent stimuli in a "spatiotopic" reference frame, linked to the location of stimuli in space (i.e., screen coordinates), independent of eye position (McKyton and Zohary, 2007;d'Avossa et al, 2007). But our results support the hypothesis that visual cortical areas represent stimulus locations in a retinotopic reference frame modulated by eye position (Gardner et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Merriam et al [88] found evidence of spatial remapping in higherorder retinotopic areas (specifically in area V3a and hV4) during the presentation of simple light flashes. McKyton & Zohary [89] tested similar questions in the object selective lateral occipital (LO) complex. They compared the fMRIa effect for man-made objects when their displacement was limited to either the retina or the screen, by manipulating eye position and object locations.…”
Section: Spatiotopic Representation and Face Aftereffects (A) Behaviourmentioning
confidence: 99%